2001
DOI: 10.1002/tcm.1031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of griseofulvin in medium‐term liver carcinogenesis assay and peripheral blood micronucleus test in rat

Abstract: Published data have suggested a possible link between the tumor promoting activity and the aneugenic properties of griseofulvin. The present study was conducted to explore this relationship. Griseofulvin was evaluated both for its potential promoting activity in liver carcinogenesis in partially hepatectomized F344 male rats initiated by diethylnitrosamine and for its genotoxic potential in the peripheral blood micronucleus assay. Rats were treated daily with 2,000 mg/kg body weight by oral gavage for 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Concerning aneugenic agents, colcemid and vincristine sulfate induced positive response in terms of MN induction containing a threshold (Table 3) which is in agreement with data reported for MN test in vivo (Cammerer et al 2010). Although, bisphenol A and griseofulvin have previously been shown to give a positive effect in other types of MN test in vitro (Hashimoto et al 2010;Johnson and Parry 2008), no effect in terms of MN induction have been reported here, which is in agreement with findings using MN test in vivo (Labay et al 2001;…”
Section: Discussionsupporting
confidence: 95%
“…Concerning aneugenic agents, colcemid and vincristine sulfate induced positive response in terms of MN induction containing a threshold (Table 3) which is in agreement with data reported for MN test in vivo (Cammerer et al 2010). Although, bisphenol A and griseofulvin have previously been shown to give a positive effect in other types of MN test in vitro (Hashimoto et al 2010;Johnson and Parry 2008), no effect in terms of MN induction have been reported here, which is in agreement with findings using MN test in vivo (Labay et al 2001;…”
Section: Discussionsupporting
confidence: 95%
“…There is some limited evidence that griseofulvin is mutagenic in the mouse lymphoma TK + /TK ) L5178Y assay (Sofuni et al, 1996). Results in the micronucleus test have generally been negative (Heddle et al, 1983;Kersten et al, 1999;Labay et al, 2001) although positive results were obtained in V79 cells and in a gut micronucleus test system (Kalweit et al, 1999;Vanhauwaert et al, 2001). Griseofulvin gave negative results in a test for DNA repair using rat and mouse hepatocytes (Mori et al, 1984) and in bacterial systems (Leifer et al, 1981).…”
Section: Griseofulvinmentioning
confidence: 99%
“…, 1983; Kersten et al. , 1999; Labay et al. , 2001) although positive results were obtained in V79 cells and in a gut micronucleus test system (Kalweit et al.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of CAbs has been considered to be important because of their known role in the induction of malignancies, congenital abnormalities, and fetal wastage (Natarajan et al, 1994; Tucker and Preston, 1996) and is thus a widely used assay for testing of the mutagenic and carcinogenic effects of environmental contaminants. Another assay, the MN test system, is also widely used in genetic toxicology studies (Labay et al, 2001). MNs are small chromatin bodies that appear in the cytoplasm by the condensation of acentric chromosome fragments or by entire chromosomes (Martinez et al, 2005).…”
Section: Discussionmentioning
confidence: 99%